2018
DOI: 10.3389/fmicb.2018.00642
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Terminal Processing of Helicobacter pylori Serine Protease HtrA: Role in Oligomerization and Activity Regulation

Abstract: The HtrA family of serine proteases is found in most bacteria, and plays an essential role in the virulence of the gastric pathogen Helicobacter pylori. Secreted H. pylori HtrA (HtrAHp) cleaves various junctional proteins such as E-cadherin disrupting the epithelial barrier, which is crucial for bacterial transmigration across the polarized epithelium. Recent studies indicated the presence of two characteristic HtrAHp forms of 55 and 52 kDa (termed p55 and p52, respectively), in worldwide strains. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 86 publications
(141 reference statements)
2
30
0
Order By: Relevance
“…Western blotting was performed onto polyvinylidene difluoride membranes (Carl Roth) by standard procedures, after the membranes were blocked with 5% milk powder in 0.2 M of Tris, 1.4 M of NaCl, 1% Tween at 4°C overnight. HtrA was detected by incubation with primary rabbit antibody α‐HtrA as previously described (Albrecht et al, ), incubated for 2 hr at room temperature, followed by incubation with horseradish peroxidase‐conjugated secondary antibody for 1 hr. The membrane was also incubated with α‐VacA and α‐FlaA antibodies as controls (Austral Biologicals, San Ramon/USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting was performed onto polyvinylidene difluoride membranes (Carl Roth) by standard procedures, after the membranes were blocked with 5% milk powder in 0.2 M of Tris, 1.4 M of NaCl, 1% Tween at 4°C overnight. HtrA was detected by incubation with primary rabbit antibody α‐HtrA as previously described (Albrecht et al, ), incubated for 2 hr at room temperature, followed by incubation with horseradish peroxidase‐conjugated secondary antibody for 1 hr. The membrane was also incubated with α‐VacA and α‐FlaA antibodies as controls (Austral Biologicals, San Ramon/USA).…”
Section: Methodsmentioning
confidence: 99%
“…pylori G27 bacteria were collected from agar plates and resuspended in prewarmed brain heart infusion medium (Oxoid) using sterile cotton swabs (Carl Roth, Karlsruhe/Germany) to OD 600 = 0.3 to start the HtrA secretion assay. primary rabbit antibody α-HtrA as previously described (Albrecht et al, 2018), incubated for 2 hr at room temperature, followed by incubation with horseradish peroxidase-conjugated secondary antibody for 1 hr. The membrane was also incubated with α-VacA and α-FlaA antibodies as controls (Austral Biologicals, San Ramon/USA).…”
Section: Htra Secretion Assay and Quantitative Western Blottingmentioning
confidence: 99%
“…The amino-terminal variations may affect the oligomerization, secretion, and regulatory activities. 23 The overexpression of HtrA did not affect the expression of other virulence proteins, such as VacA and γ-glutamyl-transpeptidase (GGT). 22 A structural similarity analysis using a DALI server, a protein structure comparison server, 24 showed that Lpp20 is very similar to the TNFα inducing protein (Tipα), with an additional short α-helix at the N-terminal.…”
Section: Non-cag Virulence Factorsmentioning
confidence: 99%
“…In addition, the HtrA activity was affected by the variation on the amino‐terminal between H46/D47 and K50/D51. The amino‐terminal variations may affect the oligomerization, secretion, and regulatory activities . The overexpression of HtrA did not affect the expression of other virulence proteins, such as VacA and γ‐glutamyl‐transpeptidase (GGT) …”
Section: Virulence Factorsmentioning
confidence: 99%
“…HtrA undergoes oligomerization and conformational changes when encountering denatured proteins, which switches on its proteolytic activity. These oligomerization and configuration processes have been studied in detail for HtrA homologs from a number of organisms, such as Thermotoga maritima [ 57 ], E. coli [ 58 , 59 ], Legionella pneumophila [ 60 ] and Helicobacter pylori [ 61 ]. Bacterial HtrAs are predominantly localized in the periplasm and de novo protein typically contains an N-terminal signal peptide that must be removed during transport across the inner membrane before the protein becomes active.…”
Section: General Structure and Function Of Bacterial Htra Proteinsmentioning
confidence: 99%